2019
DOI: 10.1111/ane.13118
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers in patients with neurological symptoms but without neurological diseases

Abstract: Background Elevated levels of the cerebrospinal fluid (CSF) neuronal injury markers (neurofilament light chain [NF‐L] and total tau protein [t‐tau]) and of the astroglial marker glial fibrillary acidic protein (GFAP) are found in etiologically different neurological disorders affecting the peripheral and the central nervous system. Aims To explore the role of CSF biomarkers in the clinical management of patients admitted for alarming neurological symptoms, but in whom neurological disorders could be excluded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It has consistently been reported that MS patients have increased levels of GFAp in CSF (Momtazmanesh et al, 2021). Several reports have also claimed that GFAp is a biomarker for progressive MS, but this is likely confounded by the strong correlation between GFAp and age (Constantinescu et al, 2019). The CSF concentrations of GFAp were somewhat higher in MS patients in comparison to the controls, most likely reflecting reactive astrocytes and astrogliosis rather than tissue damage.…”
Section: Discussionmentioning
confidence: 93%
“…It has consistently been reported that MS patients have increased levels of GFAp in CSF (Momtazmanesh et al, 2021). Several reports have also claimed that GFAp is a biomarker for progressive MS, but this is likely confounded by the strong correlation between GFAp and age (Constantinescu et al, 2019). The CSF concentrations of GFAp were somewhat higher in MS patients in comparison to the controls, most likely reflecting reactive astrocytes and astrogliosis rather than tissue damage.…”
Section: Discussionmentioning
confidence: 93%
“…Changes in NfL levels have also been linked to aging 9,17 and regional atrophy in cortical brain areas 15,18 and are therefore relatable to brain atrophy in aging among people without a recognizable neurological disease. While existing studies provide convincing evidence that serum NfL level is a promising biomarker to detect neurodegeneration in a broad range of clinical applications, the interpretation of these results has been limited by focusing analysis only on detecting the abnormal increase in serum NfL levels and by a lack of studies aimed at identifying the relevant underlying features associated with serum NfL levels 6,19 . For instance, the fundamental mechanism that links aging with serum NfL levels, even among healthy subjects, is unknown 6 .…”
mentioning
confidence: 99%
“…For instance, the fundamental mechanism that links aging with serum NfL levels, even among healthy subjects, is unknown 6 . Moreover, while serum NfL levels have been studied in controlled groups in the context of various neurological disorders, insight into the relationship between serum NfL levels and the onset of common neurological symptoms in a healthy group is still lacking 19 . Therefore, it is relevant to search for underlying features that can help ongoing neurological studies model the variance in serum NfL levels among healthy controls and thereby provide a better understanding of both baseline serum NfL levels and how abnormal variation in these levels is mechanistically linked to neurodegenerative disease through these features.…”
mentioning
confidence: 99%